PENERAPAN MEDIA CEKER UNTUK MENINGKATKAN KEMAMPUAN PENJUMLAHAN BILANGAN BULAT BAGI ANAK BERKESULITAN BELAJAR - Sonatri - Oktilia (Universitas Negeri Padang, 2012)
Against the background of this research by the apparent problems in the field, the specific learning disabilities fourth grade X class IV SD N 01 Limau Manis Padang who have difficulty in the sum of integers. This is evident from the beginning of the ability of the child in doing integer addition problems, children have difficulty in a number of the given problem and the children have not been able to answer correctly. Thus the researchers in the form of helping to improve children's ability to learn in addition disabilities through Media Ceker integers. Claw is a concrete object or a half-circle shaped plate with two different colors that can be used teachers in integer arithmetic operations. Methodology of the study is a single subject research (SSR) with a research design is AB, which compares the child's ability to sum ​​integers disabilities Baseline study on the conditions and treatment conditions. Data analysis techniques are used based on the observed data in the form of Visual Analysis Of Graph.